Det Anckerske Legats rejsestipendier for komponister 1861-1915 - Røllum-Larsen, Claus (Danish Yearbook of Musicology, 2003)
Since its establishment in 1861 “Det Anckerske Legat” has been one of the most important artists’ grants which considered composers as well. Until well into the 20th century applications for its travel grants were numerous because the relatively large grant made it possible to travel abroad for a longer period. It appears from the receivers’ travel accounts that the destinations changed during the period in question, 1861-1915. In the 19th century Leipzig dominated as an important centre of attraction, but after the turn of the century the city became less important while Paris retained a stable position as destination. Without comparison Germany has attracted most visitors throughout the whole period.